Interferențe multiculturale în „Însemnările Prințului Serghei Urusov” - Angela LISNIC (ACROSS)
The memory of the past, in the third millennium, subjected to a powerful globalization wave, comes with historical and historiographic incursions into specific aspects in the evolution of the humankind. The realms of Bessarabia boast with numerous historical pages and irrepetable events, which left an imprint on the collective unconscious of this multiethnic population. The memoir of the Russian Prince S. Urusov, which we present in this article, casts a new light on the historical past of Bessarabia, a territory whose governor he was for a short period of time (1903-1904). Though personal, this account of a descendant of a ruling family of the Russian Empire, remains a valuable source concerning the intercultural and interethnic relations in this area. The aim of this article is to comment on the multicultural interferences noted in the memorialistic account of Prince S. Urusov, and on his political notes on the multicultural spirit of Bessarabia at the turn of the twentieth century.